Development and Characterization of Plantain (Musa paradisiaca) Flour-Based Biopolymer Films Reinforced with Plantain Fibers (2022)
Agroindustrial wastes are a cheap and abundant source of natural fibers and acromolecules that can be used in the manufacturing of biocomposites. This study presents the development and thermo-mechanical characterization of a bio-composite film (TPF/PF), made of thermoplastic banana flour (TPF) matrix and plantain fibers (PF). Fabricated materials were characterized by physical analysis, chemical composition, Fourier-transformed spectroscopy (FTIR), thermal analysis (TGA), mechanical analysis, and scanning electronic microscopy (SEM). The physical analysis showed that TPF and PF have a low density and high affinity to water resulting in a lightweight, renewable, and biodegradable TPF/PF composite. The chemical composition and spectra analysis of the fiber showed that PF is a potential candidate for reinforcing composites due to its high α-cellulose and low lignin content. The thermal analysis determined that TPF degrades at a lower temperature than PF, therefore the matrix sets the processing temperature for TPF/PF composite films. The mechanical test showed an improvement in the tensile properties of the composite in comparison to neat TPF. Tensile strength and Young’s modulus were improved by 345% and 1196%, respectively, when PF fibers was used. Good bonding and mechanical interlocking of PF to the TPF were identified by SEM. Therefore, potential biocomposites can be developed using natural fibers and thermoplastic starches obtained from plantain agroindustrial wastes.